Pengembangan Bahan Ajar dengan Media Pembelajaran Scrapbook Materi Teks Biografi pada Siswa Kelas X SMA Istiqlal Deli Tua - Suhailah, Afifah; Rita, Rita; Safina, Nila; Syahputra, Ridwan (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2024)
This study aimed to depict the development, validation, and feasibility of employing Scrapbook learning media for biographical text material in class X SIVIA at SMA Istiqlal, Deli Tua. Utilizing the Research and Development (R&D) approach following the Borg and Gall model, including needs analysis, media development planning, validation, design improvement, product testing, and product revision, involving 150 students. Purposive sampling was employed, with 26 students selected. Both qualitative and quantitative data were collected. The outcome is a Scrapbook-based teaching material. Material expert validation I resulted in a "Good" categorization at 79%, while Material expert validation II reached 82%, indicating a "Good" rating. Design expert I yielded an 80% rating, also "Good," while Design expert II achieved a "Very Good" score at 86%. Teacher responses rated at 82% were deemed "Good," and student responses, totaling 87%, were "Very Good." Trial results from 26 students demonstrated improved learning outcomes using Scrapbook teaching materials.